1-year outcome of TRIAS HR (TRI-stent adjudication study - high risk of restenosis): a multicenter, randomized trial comparing genous endothelial progenitor cell capturing stents with drug-eluting stents - Klomp, Margo; Beijk, Marcel A.; Varma, Chetan; Koolen, Jacques J.; Teiger, Emmanuel; Richardt, Gert; Bea, Florian; van Geloven, Nan; Verouden, Niels J.; Chan, Yu Kwan; Woudstra, Pier; Damman, Peter; et al. (JACC Cardiovascular interventions, 2011)
Objectives - This study sought to demonstrate the noninferiority of endothelial progenitor cell capturing stents (ECS) relative to drug-eluting stents (DES) regarding target lesion failure (TLF) and the composite of cardiac death, myocardial infarction, and target lesion repeat revascularization within 1 year. - Background - A “pro-healing” approach for prevention of in-stent restenosis is theoretically favorable over the use of cytotoxic/cytostatic drugs released from DES to treat coronary artery disease. Promoting accelerated endothelialization of the stent, ECS have shown promising results in studies with patients carrying noncomplex lesions. - Methods - We undertook an international, clinical trial in 26 centers planning to randomize 1,300 patients with stable coronary artery disease and with a high risk of restenosis between treatment, with either ECS or DES. After a routine review with 50% of the patients enrolled, early cessation of the trial was recommended by the data and safety monitoring board when TLF in the ECS population was higher and treatment of new patients with an ECS would be unreasonable. - Results - At 1 year evaluating 304 patients receiving ECS and 318 receiving DES, TLF occurred in 17.4% of the ECS-treated patients and in 7.0% of the DES-treated patients (p = 0.98 for noninferiority). - Conclusions - Within 1 year, inhibition of intimal hyperplasia by the ECS is not sufficiently strong to compete with DES in terms of restenosis prevention in patients/lesions with a high risk of restenosis. Furthermore, long-term follow-up is pivotal to fully appreciate the clinical value of ECS, including the effect on late intimal hyperplasia regression.